Assessing the changing cost of Madridejos, Bantayan Islan using GIS techniques - Santos, John Christopher V.; Cortes, Aiza. (Cebu City College of Science, University of the Philippines Cebu, 2023)
Coastal erosion assessment in the municipality of Madridejos, Bantayan Island was carried out using GID techniques. The NAMRIA topographic map, IFSAR, and Google Earth satellite images were compared to analyze shoreline trend. Results revealed that the municipality is experiencing coastal erosion, which was validated by anecdotal accounts and results of geohazard and geological assessment. Coastal vulnerability assessment using Coastal Vulnerability Index (CVI) and Analytical Hierarchy Process (AHP) was also carried out in the municipality. This study augmented the ongoing Coastal Vulnerability Assessment Project in the Mines and Geosciences Bureau (MGB) by introducing socio-economic parameters in computing for overall CVI. The results revealed that 32% and 51% coastline were highly and very highly vulnerable to coastal erosion, respectively. Barangays Bunakan, Kaongkod, Poblacion, Maalat, Malbago, Mancilang, Tabagak, and Talangnan were identified to be the most vulnerable to coastal erosion and are recommended for prioritization for coastal management. A total of 17% of the coastline of Madridejos was classified as moderately vulnerable. Coastal erosion in the municipality has already resulted in loss of valuable lands and raised safety concerns to the population living along the coastal areas. The total inundation cost for the eroded coastal area was estimated to be more than 176 million Philippine pesos, which was 178% of the 2016 annual revenue of the municipality. The results and maps generated in this study will be a great tool for the LGU in formulating disaster risk reduction and management plans for their coastal areas to address the worsening effects of coastal erosion in the municipality and to ensure safety of the population of coastal barangays. The results of this study can also contribute to the Local Government Unit (LGU) of Madridejos as a baseline data in making decisions for coastal management.
Thesis (Master of Science in Environmental Science) -- University of the Philippines Cebu, January 2023